Answer:
the ordered triple of these equations will be:
(x, y, z) = (6, 1, 5)
Explanation:
Given the equations
![x + y + z = 12](https://img.qammunity.org/2021/formulas/mathematics/high-school/yy27k3kslfa5e22tlnj3xet7mzmaqfuyny.png)
![y=1](https://img.qammunity.org/2021/formulas/mathematics/college/hi20r0dca9v0qurgu6mzk81uh89xt7pohf.png)
![x - y - z = 0](https://img.qammunity.org/2021/formulas/mathematics/high-school/897ga6edisy0nzlyplzqeihugquatlgu5i.png)
As
![y=1](https://img.qammunity.org/2021/formulas/mathematics/college/hi20r0dca9v0qurgu6mzk81uh89xt7pohf.png)
We can get the value of x by adding the first and third equation
so
![x + y + z = 12](https://img.qammunity.org/2021/formulas/mathematics/high-school/yy27k3kslfa5e22tlnj3xet7mzmaqfuyny.png)
![x-y-z=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/oi5qm68aq9bgqpzid6gttzdnn7c6r4gn7s.png)
so the equations become
![x+x+y-y+z-z=12+0](https://img.qammunity.org/2021/formulas/mathematics/high-school/otwo90sxmhnnppbw0a8osrys5elxjwfwpv.png)
![2x = 12](https://img.qammunity.org/2021/formulas/mathematics/high-school/tkqb8a09x2wojxgvjosanzt7sfvw5npy0f.png)
![x = 6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/rfxeu0rgxtdic6lqlcq5waa012fmosd2e9.png)
Putting x = 6 and y=1 in the first equation
![x+y+z=12](https://img.qammunity.org/2021/formulas/mathematics/high-school/s092kuuu2dyfybg25jk2rriithb1k4jyk7.png)
![6 + 1+ z = 12](https://img.qammunity.org/2021/formulas/mathematics/high-school/u1r2f2s929xsdkfl8usbnpmr753vpqykkg.png)
![7 + z = 12\\z = 12 -7](https://img.qammunity.org/2021/formulas/mathematics/high-school/lx6j9toeh826b9s0cr3kgroa46hauecjwi.png)
![z = 5](https://img.qammunity.org/2021/formulas/mathematics/high-school/ke1xass0ofciywnofh65gijql261us9ap8.png)
Therefore, the ordered triple of these equations will be:
(x, y, z) = (6, 1, 5)